Mixed methods in promoting contraceptive decision-making after voluntary-termination-of-pregnancy - Palma, Sara; São-João, Ricardo; Antunes, Mónica; Presado, Helena (Frontiers in Global Women's Health, 2025)
AimContraception aims to protect women from unplanned and unwanted pregnancies. The number of voluntary-terminations-of-pregnancy is an indicator that highlights issues such as difficulty accessing health services and women's lack of knowledge about contraceptives. These factors complicate choosing, adhering to, continuing, and achieving satisfaction with a contraceptive method. Mixed studies have gained prominence in health research with significant implications for care quality, particularly in nursing.ObjectivesAnalyze the applicability of mixed-method research in promoting contraceptive decision-making for women undergoing voluntary termination of pregnancy.MethodsA theoretical-reflective essay based on a theoretical framework guiding reflections on mixed research. This reflection explores the basic theoretical constructs of mixed methods and their applicability in promoting contraceptive decision-making for women in the process of voluntary pregnancy termination.ResultsCategories emerging from qualitative study participants' statements were consolidated with quantitative data from women's responses to questionnaires. Integrating these two data types facilitated a robust analysis, discussion, and inference of results, leading to proposals for future interventions.ConclusionsDue to the advantages of the multimethod approach, we aim to disseminate its use in health research, demonstrating that combining quantitative and qualitative approaches provides greater insights into research phenomena and problems compared to using each method in isolation. This ultimately enhances care quality and contributes to scientific knowledge development.